Strange Case of Quarantine: Cholera Epidemic and Gothic Imagination in Rudyard Kipling's "The Strange Ride of Morrowbie Jukes" - Aqsa Eram (The Grove - Working Papers on English Studies, 2025)
This paper analyses how the gothic imagination of Rudyard Kipling, while creating a Village of the Dead that exudes disgust and horror in “The Strange Ride of Morrowbie Jukes” (1885), also inadvertently creates a quarantine space influenced by the late nineteenth-century colonial discourses of health and disease, especially that of cholera. As debates around miasma, tropical diseases and quarantine swirled in the long nineteenth century, these medical anxieties in Kipling produced a quarantine space that hinges on the notion of power, gothicized through a cultic setting. As the paper attempts to situate Kipling’s tale within the discourse of Epidemic Orientalism, it finds that the discourse coincides with interests and tropes of Imperial Gothic, conflating the cholera epidemic, Indian superstitions and the theory of degeneration to produce alterity.